The Social Organization of Community-Run Place: An Analysis of Community Gardens and Crime in Vancouver (2005–2015) - Koop-Monteiro, Yasmin (Canadian journal of criminology and criminal justice, 2021)
Community gardens can bring many benefits to community members, including access to healthy, affordable foods and opportunities for social interaction. Less certain, however, is their contribution to neighbourhood resilience to crime. To date, few studies have focused on the ability of community gardens - as distinct from other types of green spaces - to promote social organization and reduce local crime. Findings of studies that do so are inconclusive, and at best suggestive of gardens’ crime-deterring effects. The present study spotlights community gardens as unique spaces promoting social capital development and attachment to place, testing the effect of new community gardens in Vancouver, BC. Using neighbourhood census data from 2005 to 2015, the effects of new community gardens, as well as median income, population size, homeownership, and ethnic diversity, on property crime are assessed with multilevel modeling. The results show significant negative effects of median income, population size, and new community gardens on crime, with the addition of just one garden reducing neighbourhood crime by approximately 49 counts, and with increases in population size (by 1,000 individuals) and median income (by CAD$1,000) lowering crime by 48 and 34 counts, respectively.